Digital Subtraction Angiographic Pattern of Extracranial and Intracranial Atherosclerotic Arterial Stenosis among Ischemic Stroke Patients (Bangladesh Journal of Neuroscience, 2017)
Background: Stroke is the second leading cause of death in adult population throughout the world and is the most common cause of severe adult physical disability. Atherosclerotic stenosis is one of the predominant cause of ischemic stroke. The aim of this study was to evaluate the type, number and severity of intracranial and extracranial atherosclerotic stenosis and its association with different risk factors.Methods: This prospective observational study was conducted in the Department of Neurology, BSMMU, Dhaka, from July 2017 to August 2018. Only patients having significant (≥50%) symptomatic stenosis were included in this study.Results: In total 42 cases, 25 patients had extracranial stenosis, 13 patients had intracranial stenosis and 4 patients had both intracranial and extracranial stenosis. Overall 17 (40.47%) patients have intracranial involvement and 29 (69.04%) patients had extracranial involvement. The most commonly involved intracranial stenotic segment was MCA, present in 8 (32%) out of 25 intracranial segments followed by ICA 7 (28%) and intracranial vertebral artery 4(16%). Most commonly involved extracranial stenotic segment was ICA, present in 37 (77.08%) out of 48 extracranial segments. Diabetes was found to be the most common risk factor of intracranial stenosis (p value 0.022) while hypercholesterolemia was the major risk factor for severe (≥70%) stenosis.Conclusion: Extracranial arterial stenosis is more common than intracranial arterial stenosis. Anterior circulation stenosis is more common than posterior circulation stenosis. Intracranial stenosis is more prevalent in diabetic patients. Hypercholesterolemiaismore commonly seen in severe (e”70%) stenosis.Bangladesh Journal of Neuroscience 2017; Vol. 33 (2): 89-95